Observations on the Prospects for a Private University Sector in Ontario - Pike, Robert M. (Canadian Journal of Higher Education, 1991)
Unlike the United States, the Canadian provinces have established public monopolies of degree-granting institutions to which there are few private exceptions. This paper offers a case-study of challenges to the public monopoly in university education in one province—Ontario. Recently, the Ontario Council on University Affairs has been hearing the opinions of a number of interest groups and private colleges which have challenged the regulations limiting broad degree-granting privileges to the existing publicly-funded universities and their affiliates. Following a brief historical account of the development of the public monopoly, the arguments of these proponents of private universities are reviewed and evaluated under the headings of their proposed benefits of "accessibility", "diversity" and "quality". It is concluded that, from a sociologist’s perspective, the arguments for the establishment of private universities in the province are not strong. However, given the current emphasis on privatization, the pressure for private universities will probably continue to grow in all Canadian provinces. Thus, a recommendation is made for improvement of Ontario’s current inadequate affiliation arrangements.